Abnormal anatomy of the superficial branch of the radial nerve. Issue 9 (21st August 2012) - Lindau, Robert H.; Wax, Mark K.; Andersen, Peter
Abstract Background The superficial branch of the radial nerve is frequently encountered when performing the harvest for a radial forearm free tissue transfer. Methods and Results We present an abnormal course of this nerve which has not been described in the literature. During a harvest of a radial forearm free flap, we encountered a nerve that was not deep to the brachioradialis muscle in the proximal arm; rather, the superficial branch of the radial nerve was found to be superficial to this muscle through its entire course. An in‐depth literature review was performed, and there was no documented abnormality identified resembling the abnormality we encountered. Conclusion Knowledge of the normal and abnormal anatomy is essential for the microvascular surgeon to assure the safety of this nerve. © 2012 Wiley Periodicals, Inc. Head Neck, 2013